Verbal Art & TD: Tatiana Venediktova Anniversary - Andrey A. Astvatsaturov; Pavel V. Balditsyn; Sergei N. Zenkin; Artem A. Zubov; Julia B. Idlis; Grigorii M. Kruzhkov; Mikhail S. Makeev; Natalia K. Polosina; Anna V. Shvets (Литература двух Америк, 2023)
The anniversary collection of essays compiled and edited by Nataliia Polosina, Anna Shvets and Artem Zubov pays tribute to Tatiana Venediktova — Doctor of Philology, professor of American studies, founder and chair of the Department of Discourse and Communication studies at the Philological Faculty of Lomonosov Moscow University, member of the LoA editorial board. Her colleagues, friends and students contributed to the collection. Pavel Balditsyn, Julia Idlis, Mikhail Makeev, Grigoriy Kruzhkov recall the experience of cooperating with Tatiana Venediktova and working on major joint projects like the History of Literature of the United States (1997–2013) and editions of American poets in the academic book series “Literturnye Pamiatniki”. They focus on her work as a researcher, teacher, translator, publisher, academic administrator. The essays by Andrey Astvatsaturov and Sergei Zenkin commemorate the 20th anniversary of her seminal book Conversation in American: Discourse of Bargaining in the American Literary Tradition (2003). They reflect upon the impact the book had in the Russian academia back in the 2000s and its relevance for the humanities scholarship in the 2020s. The anniversary collection is a symbol of gratitude, love and respect towards Tatiana Venediktova, a recognition of her valuable contribution to the American studies and humanities in general in Russia and beyond.